Public management of sports facilities in times of austerity. Issue 1 (2nd January 2018) - Iversen, Evald Bundgaard
ABSTRACT: This article first shows how austerity has its relevance in the context of Public Management (PM) of Danish sports facilities. Then, through a qualitative explorative case-study of a particular type of sports facility, the Private Non-Profit (PNP) sports hall, the consequence of implementing PM based on New Public Governance (NPG) with the aim of increasing utilisation as a strategic response to times of austerity is analysed. A central aim of NPG is in this case to increase collaboration between local actors aiming at increasing the utilisation of sports facilities. To what extent this is possible in times of austerity is assessed by analysing the strategic behaviour of the board, management and Voluntary Sports Organisations (VSOs). Nine persons in three different sports halls representing the management, the board and the largest VSO were interviewed in 2012 and again in 2014. The results indicate that austerity measures seem to cast a shadow on attempts of increasing collaboration via NPG in times of austerity. It was very difficult to increase levels of collaboration between local actors with the aim of increasing utilisation of the sports facility. Particular attention therefore needs to be directed towards how different actors can be motivated to increase collaboration. Finally, suggestions for further research are developed.